Inguinal Hernia: Literature Review - Aritiah, Muhammad Awallul Rizky; Fariztia, Alifia Intan; Azmi, Naurah Arika; Haq, Andi Muhammad Al Fatih; Ragad, Putra; Rizaldi, Muhammad Hilman; Salsabilah, Maida Sania; Sari, Linda Silvana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Inguinal hernia is a condition when intra-abdominal fat or part of the small intestine protrudes through a weak area in the lower abdominal muscles. The purpose of this article is to discuss and learn more about inguinal hernia. This article was compiled using the literature review method in articles discussing inguinal hernia. The data or articles reviewed were obtained through searches in databases such as Google Scholar, Medscape, PubMed, and Siencedirect. The publication year limit used as a reference for compiling this article is a maximum of 10 years after publication. The results of compiling this article obtained the definition, etiology and risk factors, epidemiology, pathophysiology, clinical manifestations, diagnosis, management, complications, and prognosis of inguinal hernia. Inguinal hernia is a condition when intra-abdominal fat or part of the small intestine protrudes through a weak area in the lower abdominal muscles. The incidence of hernia according to 2005 to 2010 and Indonesia ranged from 18,145 sufferers. Hernias can be divided into direct, indirect inguinal hernias and femoral hernias based on their location. Hernias can occur due to internal and external factors. Diagnosis can be made through anamnesis, physical examination and supporting examinations. The supporting examination used is an examination using sonography. The management carried out if someone suffers from a hernia is through operative measures that are carefully prepared. Complications that can occur are scrotal edema, testicular atrophy, chronic pain after surgery, intestinal necrosis due to strangulation and complications after surgery such as femoral vein injury, ilioinguinal nerve and iliofemoral nerve. The prognosis for recurrence of hernias can be lighter in light workers and heavier in heavy workers.